The Position Of Paralegals In Providing Legal Assistance To The Defendant Is Guidance In The Trial Based On The Understanding Of The Legal Aid Law No. 16 Of 2011. - Ainun Nafik; Helvin Crismayudhi; Aji Indra Laksana; Alip Rahman; Agus Dimyati (Edunity Kajian Ilmu Sosial dan Pendidikan, 2024)
This study examines the position of paralegals in the provision of legal aid in Indonesia, especially in the context of changes regulated by Law Number 16 of 2011 concerning Legal Aid. Prior to this regulation, paralegals were not allowed to handle litigation or non-litigation cases. However, after the regulation is implemented, paralegals are permitted to provide non-litigation legal assistance. The purpose of this study is to analyze the legal position of paralegals in providing legal aid and the factors that influence them in carrying out this role. This research uses a normative juridical method with a descriptive approach based on laws and legal documents. The results of the study show that although the regulation has given authority to paralegals, there still needs to be resistance from various related parties. The main factors that affect this are the need for recognition of paralegals, the limitation of human resources, and the lack of budget and cooperation between legal stakeholders. This study concludes that further clarification is needed regarding the role of paralegals in creating equitable legal justice.